Twenty-five years development co-operation : a review - Poats, Rutherford M.; Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1985)
This is the 1985 edition of the Development Cooperation marking 25 years of the Development Assistance Committee of the Orgnisation or Economic Cooperation and Development. It provides a record of the origin and evolution of international economic cooperation and lessons for the future.
Efforts and policies of the Members of the Development Assistance Committee.
lje 04/05/2018
Ref
Keywords: Economic assistance; Technical assistance; Developing countries